Gender Differences in Self-Efficacy, Resilience, and Social Sup-port among Infertile Iranian Couples: A Dyadic Approach - Mostafa Hosseini; Mahdi Sepidarkish; Reza Omani-Samani; Saman Maroufizadeh (Tehran University of Medical Sciences, 2021)
No Abstract